Anaerobic treatment of pulp and paper industry effluent - Yusup Setiawan; Annachhatre, Ajit P.; Yang, Byung - Soo; Umita, Teruyuki; Overseas Training Office (OTO); BAPPENAS; Government of Indonesia (Bangkok : Asian Institute of Technology, 1995)
Laboratory scale experiments at average ambient temperature of 32 °C were carried out to study the feasibility of using Completely Mixed Stirrer tank Reactor (CSTR) and Upflow Anaerobic Sludge Blanket (UASB) reactor to treat sulphite pulping and bleaching wastewater. Both of UASB reactor and CSTR were inoculated by seed sludge taken from anaerobic pond treating sulphite pulping and bleaching effluent. Both reactors were fed with diluted wastewater with COD about 3000 mg/L during start-up. Feed concentration was gradually increased and finally undiluted wastewater was fed to the both reactors. CSTR start-up operation was completed within 2 months. Hydraulic Retention Time (HRT) in the range of 5.75 day to 16.73 days with corresponding on the Organic Loading Rate (OLR) in the range of 0.35 - 1.45 kg COD/m3.d was employed. COD removal efficiency in the range of 33% to 76% was obtained. Gas production rate up to 0.2 L gas/L.d was obtainable. Upflow velocities of 0.59 m/Hr to 3.86 m/Hr and Organic Loading Rate (OLR) of0.36 kg COD/m3.d to 15.58 kg COD/m3.d have been employed on UASB reactor. COD conversion up to 69.5% was obtainable. Gas production rate in the range of O. lL gas/L.d to 0.5 L gas/L.d. was obtained. External recirculation of treated effluent was necessary to achieve sludge blanket formation in UASB reactor.
Thesis (M. Eng.) - Asian Institute of Technology, 1995
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering.
Keywords: Factory and trade waste -- Purification